Analysis of the Effect of Related Party Transactions and Corporate Social Responsibility on Tax Avoidance Strategies in Infrastructure Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Rosariandoko Wijanarko, Hubertus Maria; Simon, Simon; Marojahan Sitinjak, Martogi (Green Publisher Indonesia, 2025)
This study seeks to determine the factors affecting tax avoidance in real estate and property firms. The study's population comprised real estate and property firms. This research utilized a sample of 33 real estate and property firms. Field research and library research are the methodologies employed for data collecting on the financial statements of real estate and property enterprises throughout the 2021–2023 period. The data for this inquiry was processed using Microsoft Excel and SPSS version 26. The results demonstrated that leverage and profitability substantially affect tax avoidance, although capital intensity and sales growth do not. Inspection of tax avoidance operations is advisable, as significant tax avoidance results in suboptimal state revenue.